The Anticipatory Capacity of Housing Design in Situation of Exception. Adalberto Libera in Tuscolano III - Martella, Flavio; Amann y Alcocer, Atxu; Enia, Marco (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Exceptional situations allow us to rethink sociocultural dynamics that were previously taken for granted. Architecture is often part of these processes, anticipating with its projects situations that would only occur decades later. This is the case of the Tuscolano III housing project (Rome, 1950), by Adalberto Libera, which introduces a concept of domesticity based on the dissolution between the public and the private. In this project, inhabiting is understood as a phenomenon that occurs on a neighborhood scale; and domesticity as something that expands beyond the walls of a house, and depends on a complex network of social, spatial and political relations. In Tuscolano III Libera proposes an inclusive model of the city, embracing lifestyles that were not widespread at the time, but are so in current times, such as living alone. Through this project, the article aims to investigate the anticipatory capacity of architectural design in periods of great change, as was the period of post-war reconstruction in Italy, and as is the contemporary era, with its continuing economic, political and health crises.